Brillouin–Mandelstam scattering in telecommunications optical fiber at millikelvin temperatures - E. A. Cryer-Jenkins; A. C. Leung; H. Rathee; A. K. C. Tan; K. D. Major; M. R. Vanner (APL Photonics)
Brillouin–Mandelstam scattering is a strong and readily accessible optical nonlinearity, enabling a wide array of applications and research directions. For instance, the three-wave mixing process has been employed to great success in narrow-linewidth lasers, sensing applications, microscopy, and signal processing. While most of these avenues focus on room temperature operation, there is now increasing interest in cryogenic operation owing to the scattering mechanism’s significant potential for applications and fundamental physics at low temperatures. Here, we measure the Brillouin scattering spectrum in standard single-mode telecommunication optical fibers at millikelvin temperatures using a closed-cycle dilution refrigerator and optical heterodyne detection. Our experiments are performed with a cryostat temperature from 50 mK to 27 K, extending previously reported measurements that utilized liquid helium-4 cryostats with temperatures greater than 1 K. At millikelvin temperatures, our experiment observes coherent acoustic interactions with microscopic defects in the amorphous material—two-level-systems (TLSs)—which has not been previously observed in optical fibers. The measured behavior of the linewidth with temperature is in agreement with the well-established models of ultrasonic attenuation in amorphous materials comprising a background intrinsic scattering, thermally activated scattering, and incoherent and coherent TLS interactions. This work provides a foundation for a wide range of applications and further research, including sensing applications, new approaches to investigate TLS physics, and Brillouin-scattering-based quantum science and technology.